Use of Human Resource Accounting in Taxation. - Crumbley, D. Larry; Savich, Richard S. (The Accounting Review, 1975)
Abstract Discusses a possible use of Human Resource Accounting for tax purposes in a service-related firm. Method of optimizing the distribution earnings in a closely held corporation; Standard format for determining the reasonable working capital needs for a corporation; Application of the mathematical Bardahl formula in the case Simons-Eastern Co. v. U.S.; Human Resource formula for service organizations.